2021
DOI: 10.3389/fphar.2021.717023
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Versus Propofol for Patients With Sepsis Requiring Mechanical Ventilation: A Systematic Review and Meta-Analysis

Abstract: Purpose: This meta-analysis was performed to access the influence of dexmedetomidine versus propofol for adult patients with sepsis undergoing mechanical ventilation.Materials and Methods: NCBI PUBMED, Cochrane Library, Embase, China National Knowledge Internet (CNKI), and China Biological Medicine (CBM) were searched. Revman 5.3 and Stata software (version 12.0, Stata Corp LP, College Station, TX, United States) were used for meta-analysis.Results: Fifteen studies were included, and the data from the included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
(31 reference statements)
0
6
1
Order By: Relevance
“…Our outcomes were different from that of several similar previous meta-analyses ( Zhang et al, 2019 ; Chen et al, 2020 ; Huang et al, 2021 ; Wang et al, 2021 ; Abdelazeem et al, 2022 ; Liu et al, 2022 ). Chen et al ( Chen et al, 2020 ) reported that DEX increased the number of ventilator-free days and reduced 28-day mortality for sedation among mechanically ventilated adult sepsis or septic shock patients, and Zhang et al ( Zhang et al, 2019 ) concluded that dexmedetomidine could dramatically reduce 28-day mortality.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our outcomes were different from that of several similar previous meta-analyses ( Zhang et al, 2019 ; Chen et al, 2020 ; Huang et al, 2021 ; Wang et al, 2021 ; Abdelazeem et al, 2022 ; Liu et al, 2022 ). Chen et al ( Chen et al, 2020 ) reported that DEX increased the number of ventilator-free days and reduced 28-day mortality for sedation among mechanically ventilated adult sepsis or septic shock patients, and Zhang et al ( Zhang et al, 2019 ) concluded that dexmedetomidine could dramatically reduce 28-day mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, their interventions of the control group were broad, including sedatives such as midazolam and lorazepam. Although four meta-analyses ( Huang et al, 2021 ; Wang et al, 2021 ; Abdelazeem et al, 2022 ; Liu et al, 2022 ) draw the similar primary outcome as we were in the previous year, we believed that our present study was more persuasive than those because of the larger sample size and the more specific control group. As the rigorous eligibility criteria we designed, our present meta-analysis, including 1,212 patients and setting propofol intervention principally for the control group, rendered the results more convincing.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Several systematic reviews and meta-analyses on this research topic have been previously conducted [ 11 ] [ 12 ] [ 13 ] [ 49 ] [ 14 ]. Among previous meta-analyses, Huang et al was the most comprehensive study [ 13 ], and it included 15 RCTs with 1,871 patients in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent four meta-analyses have shown controversial results, where two of these studies [ 11 ] [ 12 ] suggested a positive effect of dexmedetomidine on mortality in sepsis patients, while two other studies [ 13 ] [ 14 ] did not find a significant difference in mortality between dexmedetomidine and the other sedative agents. However, these conclusions are limited by the number of included studies, and the effects of dexmedetomidine on the incidence of delirium, adverse events, and the length of intensive care unit (ICU) stay remains controversial.…”
Section: Introductionmentioning
confidence: 99%